1998
DOI: 10.1143/jjap.37.2098
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Doping Effect on Phase Change Optical Disks

Abstract: The nitrogen doping effect on the Ge–Sb–Te recording layer was quantitatively examined. We succeeded in the quantitative analysis of the nitrogen concentration in the Ge–Sb–Te–(N) recording layer by secondary ion mass spectrometry (SIMS) observation. The nitrogen concentration could be finely controlled at a high deposition rate of 4.7 nm/s. The addition of a small amount of nitrogen remarkably improved the overwrite cycle numbers. We found that the most suitable nitrogen concentration was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 114 publications
(60 citation statements)
references
References 2 publications
2
57
1
Order By: Relevance
“…The increase of the crystallization temperature in oxygen (Jeong et al, 2001) and nitrogen [Kojima et al, 1998, Jeong et al, 2000 doped GST has been already reported in literature, as well as the reduction of the grain size in samples containing nitrogen. Several models have been proposed (Jeong et al, 2001, Jeong et al, 2000 trying to simultaneously explaining the effect of both O and N in order to find the optimal dopant to engineer specific properties of GST.…”
Section: Wwwintechopencomsupporting
confidence: 57%
See 2 more Smart Citations
“…The increase of the crystallization temperature in oxygen (Jeong et al, 2001) and nitrogen [Kojima et al, 1998, Jeong et al, 2000 doped GST has been already reported in literature, as well as the reduction of the grain size in samples containing nitrogen. Several models have been proposed (Jeong et al, 2001, Jeong et al, 2000 trying to simultaneously explaining the effect of both O and N in order to find the optimal dopant to engineer specific properties of GST.…”
Section: Wwwintechopencomsupporting
confidence: 57%
“…In fact, it has been shown that nitrogen doping during deposition (Kojima et al 1998, Jeong et al 2000 increases the amorphous stability and reduces the grain size, improving the cell cyclability.…”
Section: Phase Change Memorymentioning
confidence: 99%
See 1 more Smart Citation
“…It is apparent respectively in the left-and right-hand triangles that T x is far higher than room temperature and t cry is sufficiently short, <50 ns. By the environmental acceleration tests on the real optical disk device using the Arrhenius method, the estimated lifetime of the amorphous marks formed in the crystalline GeSbTe was more than several tens of years at room conditions (308C, 80% RH) [10]. It is amazing that the ratio between the estimated lifetime (30 years) and the laser crystallization time (30 ns) reaches 10 [17][18] .…”
Section: Crystallization Propertiesmentioning
confidence: 99%
“…Nitrogen doping was utilized to increase the temperature of crystalline in the film. [16][17][18][19][20] After fabricating PCM devices with island cells of 200 nm in diameter, the electrical properties of the devices were evaluated in terms of the characteristics of the material, compared with corresponding findings for 7 at% nitrogen doped Ge 2 Sb 2 Te 5 materials. The optimum composition of GeBiTe film together with nitrogen incorporation resulted in the production of a potentially promising phase change material for use in high performance PCM and forthcoming SCM applications.…”
Section: Introductionmentioning
confidence: 99%